2019
DOI: 10.7759/cureus.3857
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal Effect of Radiotherapy in Imatinib-resistant Dermatofibrosarcoma Protuberans

Abstract: Local tumor control and symptom relief have been the major advantage of radiotherapy in clinical practice. In the past years, the systemic anti-tumor effect of radiotherapy, also known as the abscopal effect, has been reported with limited studies. With the advent of immunotherapy, the frequency of the abscopal effect has increased in patients who receive sequential treatment with radiotherapy and immunotherapy or patients who receive radiotherapy after acquiring resistance to immunotherapy. A novel cancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Multiple studies have shown that DFSP is a radio-responsive tumor and adjuvant radiation therapy is effective to control tumor growth and reduce the incidence of postoperative recurrence [102][103][104][105][106]. A retrospective analysis of 53 DFSP patients treated with surgery and either preoperative or postoperative radiation therapy in the MD Anderson Cancer Center showed disease-free survival rates of 98% and 93% at 5 and 10 years, respectively [105].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Multiple studies have shown that DFSP is a radio-responsive tumor and adjuvant radiation therapy is effective to control tumor growth and reduce the incidence of postoperative recurrence [102][103][104][105][106]. A retrospective analysis of 53 DFSP patients treated with surgery and either preoperative or postoperative radiation therapy in the MD Anderson Cancer Center showed disease-free survival rates of 98% and 93% at 5 and 10 years, respectively [105].…”
Section: Radiation Therapymentioning
confidence: 99%
“…50 studies (n=55 subjects) published from 1954 -2019 met inclusion criteria and were used. 23,24,[33][34][35][36][37][38][39][40][41][42]25,[43][44][45][46][47][48][49][50][51][52]26,[53][54][55][56][57][58][59][60][61][62]27,[63][64][65][66][67][68][69][70][71][72]28,[73][74][75][76][77][29][30][31][32] The median patient age was 65 years (interquartile range, IQR: 57-70); 34 (62%) males and 21 (...…”
Section: Resultsmentioning
confidence: 99%
“…(1) Prior treatment courses were as follows (treatments in this phase were not mutually exclusive): 9 (16%) had radiotherapy, 28,33,38,41,46,53,64,73,75 26 (47%) had surgery, 23,24,45,48,[53][54][55]61,[67][68][69][70]28,71,[75][76][77]31,33,[38][39][40][41][42] 23 (42%) had chemotherapy, 23,27,42,48,49,51,53,56,60,64,68,69,28,[71][72][73]31,32,35,36,38,40,41 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, tumors with close or positive surgical margins, recurrent tumors, metastatic tumors, and large unresectable tumors are treated with radiation therapy and systemic therapy as adjuvant treatment modalities [ 5 ]…”
Section: Introductionmentioning
confidence: 99%